Acute myocarditis associated with non-typhoidal Salmonella gastroenteritis - Sehun Choi; Jae Sung Son; Hee-Won Moon; Soo-Jin Kim; Hye Won Park; Ran Lee (Pediatric Emergency Medicine Journal, 2019)
Acute myocarditis is clinically rare in children, but poses a significant risk for morbidity and mortality. Children with myocarditis show a wide variety of clinical manifestations ranging from subclinical myocarditis to heart failure, hemodynamic compromise, arrhythmia, and even sudden death. Salmonella species are associated with clinical presentations including gastroenteritis, enteric fever, bacteremia, and extra-intestinal focal infections. Non-typhoidal Salmonella infections usually cause self-limiting gastroenteritis, but are rarely associated with myocarditis. In this report, we present a case of myocarditis associated with Salmonella serogroup B gastroenteritis in a previously healthy 15-year-old boy.